Comparison of effects of two analgesia methods on surgery for developmental dysplasia of the hip in children - Peng, Bing; Zhang, Xifeng; Gu, Li; Jiang, Wenxu (Vojnosanitetski pregled, 2024)
Background/Aim. Surgery for developmental dysplasia of the hip (DDH) often needs acetabuloplasty and femoral osteotomy. This type of operation is characterized by long duration, major trauma, and severe postoperative pain. The aim of the study was to compare the analgesic effects of the caudal block (CB) and epidural block (EB) on the DDH surgery in children. Methods. A total of 100 children undergoing DDH surgery in our hospital from May 2018 to December 2021 were selected and randomly divided into two groups: an ultrasound-guided CB group and an EB group (each group consisting of 50 children). The dosage of ropivacaine, changes in blood pressure, heart rate, and intraoperative dosage of fentanyl were recorded. In addition, we recorded the values of several parameters after the surgery: the modified Face, Legs, Activity, Cry, and Consolability (FLACC) scale score at 2, 4, 6, 12, 24, 36, and 48 hrs after surgery; the time point of first-time request for acetaminophen and proportion of patients using pethidine; the sedation degree within 12 hrs after the operation (assessed using the Ramsay Sedation Scale – RSS); the incidence of nausea, vomiting, and urinary retention; the satisfaction degree of family members with the applied methods of postoperative analgesia in children. Results. The ropivacaine dosage used in the CB group exceeded that of the EB group (p < 0.05). The CB group had lower FLACC scores 12 and 24 hrs after the operation and a longer postoperative time until the first-time request for acetaminophen than the EB group (p < 0.05). No block-related complications occurred; the two groups had similar incidence rates of nausea, vomiting, and urinary retention. The RSS score within 12 hrs after operation was higher in the CB group than in the EB group, and the family members of the children in the CB group were more satisfied (p < 0.05). Conclusion. Both CB and EB can provide satisfactory intraoperative and postoperative analgesia for pediatric hip surgery. However, CB provides effective analgesia for 24 hrs after the operation and lasts longer than that accomplished by the EB.